From menstruation to the menopause : the female fertility cycle in contemporary women's writing in French - Tomlinson, Maria Kathryn (Contemporary French and francophone cultures., 2021)
This book examines menstruation, childbirth, and the menopause in contemporary Algerian, Mauritian, and French women's writing. It looks back to the pioneering work of the second-wave feminists and argues that contemporary women's writing has continued to challenge normative perceptions whilst also taking a more intersectional approach to corporeal experience.